Epidemiological situation of maternal deaths in Peru during 2015 and 2022 and analysis of two decades of years of life potentially lost. - Rueda-Camaná, Manuel (2025)
Introduction: Maternal mortality (MM) is considered a public health problem and is regarded as an indicator for global health status. The objective of this study was to determine the epidemiological situation of MM by calculating the maternal mortality ratio (MMR) and years of potential life lost (YPLL) in Peru from 2002 to 2022. Methods: A study was conducted using data from the Maternal Mortality Situational Room and the National Institute of Statistics and Informatics. MMR were calculated annually at both the national and departmental levels from 2015 to 2022, while YPLL were calculated for each year between 2 002 and 2 022 based on data availability. Results: The highest MMR was observed in 2 021 at 106.56. The departments with the highest MMRs in 2022 were Amazonas with 173.31 and Loreto with 117.48. Tacna and Moquegua had annual periods with no maternal deaths. Between 2002 and 2022, a total of 429,881.21 YPLLs were recorded, with 2022 having the lowest number of YPLLs at 13,932.43. The coefficient of determination was 0.57, indicating a decreasing trend. Conclusions: Maternal mortality showed a decrease over the study years, except for 2020 and 2021. Inequities persist among departments, with a significant difference in MMRs. YPLLs also significantly decreased over the study period. The age group with the highest loss was victims aged 20 to 24 years.